An investigation of the energy and environmental sustainability impact of affordable net-zero energy house in South Africa - Hübner, Dylan (Department of Construction Economics and Management, 2025)
This dissertation is submitted in fulfilment of the requirements for the degree of Master of Philosophy (MPhil) in Construction Economics and Management at the University of Cape Town. This study aims to explore the energy and environmental sustainability implications linked to affordable net-zero energy housing in South Africa. Affordable housing is intended for individuals who cannot afford market related prices or do not meet the criteria for social housing. Accordingly, this dissertation defines affordability as households spending no more than 30% of their income on gross housing expenses. It seeks to provide insights into the challenges, opportunities, and implications of integrating net-zero energy housing into the affordable housing sector. Given South Africa's shortage of affordable housing, unstable electricity supply, and economic challenges, there is significant opportunity to explore alternative building strategies to address these issues. The research employed an exploratory mixed-method approach rooted in the philosophical foundations of realism. Qualitative data was procured through 4 in-depth semi-structured interviews conducted with 3 sustainability professionals and an affordable housing specialist. Quantitative modelling utilised One Click LCA and the Edge App to estimate the life cycle carbon emissions of an affordable net-zero energy house. The findings indicate that affordable net-zero energy housing can substantially reduce both operational and embodied carbon emissions. By integrating conventional building practices with innovative methods, the life cycle emissions of a house are significantly reduced, surpassing sustainable building regulation requirements. The quantitative analysis of three affordable net-zero energy housing scenarios, incorporating both conventional and innovative building techniques and practices across different levels to mimic South Africa's construction landscape, demonstrates a potential reduction in life cycle carbon emissions ranging from 12% to 94%. Furthermore, South Africa's landscape may not be conducive to net-zero embodied energy houses, suggesting that developers and households should prioritise reducing operational carbon emissions. These findings contribute to knowledge within the professional, affordable, and sustainable housing spaces, thereby facilitating informed decision-making towards a more sustainable and affordable South African residential sector.